The N-terminal acetylation of Sir3 stabilizes its binding to the nucleosome core particle - Arnaudo, Nadia (2013)
The N-terminal acetylation of Sir3 is essential for heterochromatin establishment and maintenance in yeast, but its mechanism of action is unknown. The crystal structure of the N-terminally acetylated BAH domain of Saccharomyces cerevisiae Sir3 bound to the nucleosome core particle reveals that the N-terminal acetylation stabilizes the interaction of Sir3 with the nucleosome. Additionally, we present a new method for the production of protein–nucleosome complexes for structural analysis.